“I Want to Go to Another Land”. A.E. Stallings and the Poetry of Exile - Dowling, Gregory (Oltreoceano - Rivista sulle migrazioni, 2021)
This paper examines three versions of Cavafy’s poem, “The City”, by the American poet, A.E. Stallings. Stallings, since 1999 resident in Greece, has often addressed issues of home and exile. Her different versions show not only a development in her attitude towards translation but also a growing awareness of the universality of Cavafy’s great poem on exile. “Voglio andare in un’altra terra”. A. E. Stallings e la poesia dell’esilio Questo saggio esamina tre diverse traduzioni della poesia “La città” di Kavafis da parte della poetessa americana A. E. Stallings. La poetessa, residente dal 1999 in Grecia, si occupa da tempo del tema dell’esilio. Le diverse versioni dimostrano non soltanto una riconsiderazione del modo di tradurre, ma anche una crescente consapevolezza dell’universalità di questa grande poesia sull’esilio.